Living in the Rocky Mountain West, 2025: series preview - Colorado Institute of Public Policy, author (Colorado State University. Libraries, 2005)
The Rocky Mountain West is an area of unique resources and opportunities. This paper introduces a series of six white papers forthcoming from the Colorado Institute of Public Policy. Paper topics include: Water, Demographics, Energy, Governance, Public Health, and Development.
Published in August 2005.
Keywords: Demography -- West (U.S.); Land use -- West (U.S.); Health -- West (U.S.); Water use -- West (U.S.); Lifestyles -- Rocky Mountains; Mountains -- West (U.S.)